Study on the evolution of olive price in Romania - Ionut Laurentiu Petre (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
It is appreciated that the olives in Romania have recorded higher prices, so in this paper it is desirable to analyse exactly the evolution of the prices for the olives, but also the main factors that can influence these changes, such as import prices, the situation of the areas and production in these exporting countries and the correlations between these data. Through the statistical website at European level, Eurostat, it was possible to analyse the price evolutions for olives in the EU member countries, but especially for those from which Romania imports this product. Prices, olive-growing areas in these countries and yields on these areas were analysed. Finally, the relationship between these indicators and the price of olives sold in Romania will be analysed in terms of the intensity of the link.
Keywords: !11; Q17; 330; olives; price; productions; surfaces; exporters